Platelet Activation and the Immune Response to Tuberculosis - Kirwan, Daniela E.; Chong, Deborah L. W.; Friedland, Jon S. (Frontiers in Immunology, 2021)
In 2019 10 million people developed symptomatic tuberculosis (TB) disease and 1.2 million died. In active TB the inflammatory response causes tissue destruction, which leads to both acute morbidity and mortality. Tissue destruction in TB is driven by host innate immunity and mediated via enzymes, chiefly matrix metalloproteinases (MMPs) which are secreted by leukocytes and stromal cells and degrade the extracellular matrix. Here we review the growing evidence implicating platelets in TB immunopathology. TB patients typically have high platelet counts, which correlate with disease severity, and a hypercoagulable profile. Platelets are present in human TB granulomas and platelet-associated gene transcripts are increased in TB patients versus healthy controls. Platelets most likely drive TB immunopathology through their effect on other immune cells, particularly monocytes, to lead to upregulation of activation markers, increased MMP secretion, and enhanced phagocytosis. Finally, we consider current evidence supporting use of targeted anti-platelet agents in the treatment of TB due to growing interest in developing host-directed therapies to limit tissue damage and improve treatment outcomes. In summary, platelets are implicated in TB disease and contribute to MMP-mediated tissue damage via their cellular interactions with other leukocytes, and are potential targets for novel host-directed therapies.